Tunicamycin induced inhibition of calpain 1 and 2 enzyme activity in ovarian cancer cells - Sari Kilicaslan, Seda M.; Zerrin İncesu (International Journal of Basic & Clinical Pharmacology, 2023)
Background: Tunicamycin (TN) is an antitumor agent and induced intracellular calcium levels in many cells, however its molecular mechanism is still needed to be explored. Calpeptin (Calp) is an inhibitor of both calpain 1 and 2 (CAPN-1/2) enzymes, and plays a fundamental role in tumor mechanism. In this study, the effects of TN and Calp were investigated on CAPN-1/2 enzyme activity in normal and ovarian cancer cells adhered to fibronectin. Methods: 24uM TN, 50uM Calp, and combined TN and Calp (TN+Calp) were applied for 1 and 12 hours to FN-bound (FN+) and non-FN-bound (FN-) normal human ovarian epithelial (IHOSE) and ovarian cancer (SKOV-3) cells. The activation of CAPN-1/2 was measured by the luminescent method and the significance of the results was analyzed with the t-test. Results: CAPN-1/2 enzyme activity (at 12 hour) was present in both cell lines, but the level of enzyme is higher in IHOSE cells compared to SKOV-3 cells. The results showed that 1 hour TN and TN+Calp applications stimulated CAPN-1/2 enzyme activity in IHOSE cells but did not show any stimulating effect in SKOV-3 cells. After 12-hour of treatment, the cells with TN, Calp or TN+Calp showed an inhibitory effect on CAPN-1/2 enzyme in both FN+IHOSE and SKOV-3 cells. At 12-hour TN+Calp administration was determined to be the most effective inhibitor in FN+ SKOV-3 since it inhibited CAPN1/2 activity statistically significantly more than both Calp and TN administrations. Conclusions: The effects of TN, Calp and TN+Calp applications on the CAPN-1/2 enzyme varied according to the cell type, normal or cancer cells, and whether the cell was bound to FN and the incubation period. 12 h administrations of TN, Calp or TN+Calp inhibited the CAPN-1/2 enzyme in both FN+ IHOSE and SKOV-3 cells.